2017
DOI: 10.18632/oncotarget.16452
|View full text |Cite
|
Sign up to set email alerts
|

Syntenin promotes VEGF-induced VEGFR2 endocytosis and angiogenesis by increasing ephrin-B2 function in endothelial cells

Abstract: Syntenin, a tandem PDZ-domain-containing scaffold protein, is involved in the regulation of diverse biological functions, including protein trafficking, exosome biogenesis, and cancer metastasis. Here, we present the first study to explore the significance of syntenin in endothelial cells. Syntenin knockdown in human umbilical vein endothelial cells (HUVECs) impaired vascular endothelial growth factor (VEGF)-mediated proliferation, migration, invasion, vascular permeability, and nitric oxide (NO) production. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
(79 reference statements)
2
22
0
2
Order By: Relevance
“…Cav-1 can also combine with TβR-1 to induce its internalization and further cause its degradation mediated by ubiquitin-proteosome, thus blocking TGF-β signaling pathway. In contrast, syntenin, a scaffold protein that can interact with multiple membrane receptors, is able to prevent TβR-1 internalization and degradation by disassociating the TβR-1/Cav-1 complex, finally to facilitate lung cancer progression [86,87]. A metastasis-associated protein called EF-hand domain-containing protein D2 (EFHD2) is found to inhibit Cav-1 mRNA and protein expressions, and subsequently upregulate Snail and Vimentin as well as downregulate E-cadherin in A549 cells to enhance EMT.…”
Section: Cav-1 and Emtmentioning
confidence: 99%
“…Cav-1 can also combine with TβR-1 to induce its internalization and further cause its degradation mediated by ubiquitin-proteosome, thus blocking TGF-β signaling pathway. In contrast, syntenin, a scaffold protein that can interact with multiple membrane receptors, is able to prevent TβR-1 internalization and degradation by disassociating the TβR-1/Cav-1 complex, finally to facilitate lung cancer progression [86,87]. A metastasis-associated protein called EF-hand domain-containing protein D2 (EFHD2) is found to inhibit Cav-1 mRNA and protein expressions, and subsequently upregulate Snail and Vimentin as well as downregulate E-cadherin in A549 cells to enhance EMT.…”
Section: Cav-1 and Emtmentioning
confidence: 99%
“…Recent studies show that VEGFR2 endocytosis is indispensable for VEGFR2 signal transduction 8 , 9 . VEGFR2 internalization is reported to be regulated by Ephrin-B2, and its interacting protein, Dab2 (clathrin-associated protein disabled 2) as well as the cell polarity protein PAR-3 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase of HIF-1 α reflects the occurrence and progress of cancer [33]. HIF-1 α and VEGF overexpressed in lung cancer are secreted into the blood and can be used to diagnose the cancer [34], Syntenin is shown to inhibit apoptosis [35] and inhibition of syntenin will reduce the activity of VEGF [19]. In melanoma, syntenin induces angiogenesis by activating Akt, leading to the expression of HIF-1α and the transcription of IGF-binding protein-2 (IGFBP-2), which induces the production of VEGF in endothelial cells and angiogenesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the up-regulation of syntenin promotes the migration of non-metastatic cancer cells [16], and knockdown of syntenin inhibits the migration and invasion of cells [17,18]. In addition, syntenin has been shown to promote the formation of blood vessels [19]. VEGF has been demonstrated to be an important physiological and pathological factor for angiogenesis and play an important role in the occurrence and development of tumor [20].…”
Section: Introductionmentioning
confidence: 99%